2022
DOI: 10.3389/fendo.2022.861422
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitor treatment is not associated with an increased risk of osteoporotic fractures when compared to GLP-1 receptor agonists: A nationwide cohort study

Abstract: BackgroundType 2 diabetes mellitus (T2D) is associated with an increased fracture risk. It is debated whether sodium-glucose cotransporter 2 (SGLT2) inhibitors influence fracture risk in T2D. We aimed to investigate the risk of major osteoporotic fractures (MOF) with SGLT2 inhibitors compared to glucagon-like peptide 1 (GLP-1) receptor agonists when used as add-on therapies to metformin.MethodsWe conducted a population-based cohort study using Danish national health registries. Diagnoses were obtained from dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…On the other hand, observational studies may have longer treatment duration. As shown in the recent epidemiological studies assessing GLP-1 RA and fractures, there are reported neutral outcomes compared to DPP4-i and SGLT-2i [30 ▪ ,31 ▪ ]. This is in alignment with previous studies and therefore treatment with GLP-1 RA in individuals with type 2 diabetes is perceived as fracture neutral [36,50,51].…”
Section: Evidence Within the Recent Yearsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, observational studies may have longer treatment duration. As shown in the recent epidemiological studies assessing GLP-1 RA and fractures, there are reported neutral outcomes compared to DPP4-i and SGLT-2i [30 ▪ ,31 ▪ ]. This is in alignment with previous studies and therefore treatment with GLP-1 RA in individuals with type 2 diabetes is perceived as fracture neutral [36,50,51].…”
Section: Evidence Within the Recent Yearsupporting
confidence: 81%
“…Two propensity score matched cohort studies, based on Danish national registries, found no difference in fracture rates between users of DPP4-I and GLP-1 RA, or between users of sodium glucose co-transporter-2 inhibitors and GLP-1 RA when using these drugs as an add on to metformin [30 ▪ ,31 ▪ ]. However, there was an association towards lower fracture rates among those treated with the highest doses of GLP-1 RA compared to DPP4-I [30 ▪ ].…”
Section: Evidence Within the Recent Yearmentioning
confidence: 99%
“…The current use of metformin plus SGLT-2 inhibitor compared to the current use of metformin plus DPP-4 inhibitor was not associated with fractures in patients with type 2 diabetes ( 73 ). SGLT2 inhibitors + metformin combination treatment do not affect fracture risk compared to GLP-1 receptor agonists + metformin combination ( 74 ). SGLT2 and metformin combination therapy did not influence fracture risk compared with metformin monotherapy or other medications in patients with T2DM ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of our study are supported by several other studies, including randomized controlled trials, all pointing towards a neutral effect of SGLT2 inhibitor use on fracture risk. [24][25][26][27][28][29][30] Our study used the CPRD database, which includes up to 19.9% (Aurum database) of the total population in the United Kingdom, 16 and did not find an increased fracture risk with SGLT2 inhibitor use versus DPP-4 inhibitor use in either Aurum or GOLD. This is also in line with a recent meta-analysis, 31 which included 11 large randomized clinical trials of this drug class in their meta-analysis on the association between SGLT2 inhibitor and fracture risk and concluded the CANVAS results were likely due to chance.…”
Section: Discussionmentioning
confidence: 99%